EVALUASI PROPERTI PSIKOMETRI INSTRUMEN GRIT AKADEMIK VERSI PENDEK TERJEMAHAN BERBAHASA INDONESIA (GRIT-S) - Yonathan Natanael; Muhamad Ansori; Anggun Marsela; Sabrina Aldini Maharani; Fadilla Nurazizah (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2025)
The short version Grit-Scale was validated in Indonesia when 2019 by testing internal validity using confirmatory factor analysis (CFA) only on the sampled instrument. Suppose an instrument test is only focused on testing internal validity. In that case, it is inevitable that the research only meets the slight evidence of instrument validity recommended by institutions recognized by the science of Education and Psychology. Therefore, this study aims to evaluate the psychometric properties of the Indonesian version of Grit-S by combining two validity methods, namely internal and external validity testing. The research participants consisted of 450 students from various universities and faculties in Indonesia, aged 17 to 25 years, which were obtained by convenience sampling. The findings in this study prove that the Indonesian version of Grit-S is a reliable instrument, the excellent factor structure is the two-factor model, it meets the criteria of external validity where the Indonesian version of Grit-S converges when tested with self-esteem and life satisfaction scales, as well as all the Indonesian version of Grit-S items does not indicate gender bias. The Indonesian version of Grit-S is very feasible and allows it to be used for research in the fields of Education and Psychology in Indonesia